The effect of annealing to the hardness of high Y2O3-oxide dispersion strengthened (ODS) ferritic steels - Shamsudin F.M.; Radiman S.; Abdullah Y.; Hamid N.A. (Penerbit Universiti Kebangsaan Malaysia, 2023)
alloy; annealing; compaction; dispersion; electron microscopy; hardness; oxide; steel; X-ray diffraction; yttrium